ADVANCED MATHEMATICS FORM 6 – VECTOR ANALYSIS- 2

Share this post on:

 edu.uptymez.com2 = edu.uptymez.com2 + edu.uptymez.com2 – 2 edu.uptymez.com edu.uptymez.com cos edu.uptymez.com

Therefore

edu.uptymez.com2 = edu.uptymez.com2 + edu.uptymez.com2 – 2 edu.uptymez.com edu.uptymez.com cos edu.uptymez.com

02. USED TO FIND THE PROJECTION OF ONE VECTOR ONTO ANOTHER  VECTOR

–      Suppose the projection of a onto b

i.e
edu.uptymez.com                                                                                                                                                                                                                                                                       

Cos Q =  edu.uptymez.com

Cos Q = edu.uptymez.com

proj edu.uptymez.com = edu.uptymez.com cos Q        ———– i

Also

 edu.uptymez.com . edu.uptymez.com = edu.uptymez.com edu.uptymez.com  cos Q

 edu.uptymez.com = edu.uptymez.com cos Q            ———–ii

Equalizing i and ii as follows;

    proj edu.uptymez.com = edu.uptymez.com cos Q = edu.uptymez.com

     proj edu.uptymez.com = edu.uptymez.com

similary

    proj edu.uptymez.com = edu.uptymez.com

Where;

Proj edu.uptymez.com = projection of edu.uptymez.com onto edu.uptymez.com

Proj edu.uptymez.com = projection of edu.uptymez.com onto edu.uptymez.com

VECTOR PROJECTION

This is given by

V projedu.uptymez.com =edu.uptymez.com. edu.uptymez.com

          And

V. projedu.uptymez.com =edu.uptymez.com. edu.uptymez.com

Where;

V. proj edu.uptymez.com = vector projection of edu.uptymez.com onto edu.uptymez.com

V. proj edu.uptymez.com = vector projection of edu.uptymez.com onto edu.uptymez.com

03. TO FIND THE WORKDONE

          – Consider the diagram below                                                                                       

edu.uptymez.com

 edu.uptymez.com                                                                                                                                                                                         

          Force applied (F) = component of tone

           cos Q = edu.uptymez.com

          Cos Q = edu.uptymez.com

          F = edu.uptymez.com Cos Q

          Also

Distance d = edu.uptymez.com

          d = edu.uptymez.com….ii

Hence

Work done = Force applied (F) x distance (d)

          W.D = F x d

          W. D = edu.uptymez.com cos Q x edu.uptymez.com

                   = edu.uptymez.com cos Q

                   = edu.uptymez.com. edu.uptymez.com 

          W.D = edu.uptymez.com

Note

i) Force F in the direction of vector edu.uptymez.com

Force applied = F.edu.uptymez.com

ii) Distance in the direction of vector edu.uptymez.com

          Displacement edu.uptymez.com = d.edu.uptymez.com

Individual 

i) edu.uptymez.com = 2i + edu.uptymez.com + 2edu.uptymez.com

          edu.uptymez.com = i + edu.uptymez.com + edu.uptymez.com

          W.D = edu.uptymez.com

04. TO PROVE COMPOUND ANGLE FORMULA OF COSINE

i.e cos (A + B) = cos A cos B – sin A sin B

edu.uptymez.com– consider the vector diagram below.

 Diagram

       edu.uptymez.com                                                        

 edu.uptymez.com = (cos A) edu.uptymez.com + (sin A) edu.uptymez.com

 edu.uptymez.com = (cos B) edu.uptymez.com – (sin B) edu.uptymez.com

Hence

 edu.uptymez.com edu.uptymez.com = edu.uptymez.com cos (A + B)

                        but

 edu.uptymez.com. edu.uptymez.com = edu.uptymez.com edu.uptymez.com

          = cos A cos B + -sin A sin 0

          = cos A cos B – sin A sin B

Also

 edu.uptymez.com = edu.uptymez.com

          = edu.uptymez.com

                   = edu.uptymez.com

                    = 1

 edu.uptymez.com =  edu.uptymez.com

          = edu.uptymez.com

                   = edu.uptymez.com

                    = 1

Therefore

Cos A cos B – sin A sin B = (1)(1) cos (A + B)

Cos (A + B) = cos A cos B – sin A sin B

          Proved

Pg. 2 drawing

 edu.uptymez.com

 edu.uptymez.com = (cos A) edu.uptymez.com + (sin A) j

 edu.uptymez.com = (cos B) I + (sin B) edu.uptymez.com

    Hence

 edu.uptymez.comedu.uptymez.com = edu.uptymez.com edu.uptymez.comcos (A – B)

          But

 edu.uptymez.comedu.uptymez.com = edu.uptymez.com edu.uptymez.com

     edu.uptymez.comedu.uptymez.com = cos A cos B + sin A sin B

                        Also

      edu.uptymez.com = edu.uptymez.com

          = edu.uptymez.com

                   = edu.uptymez.com

                    = 1

edu.uptymez.com =  edu.uptymez.com

          = edu.uptymez.com

                   = edu.uptymez.com

                    = 1

          There
          Cos A cos B + sin A sin B = (1) (1) cos (A – B)
 
          Cos (A – B) = cos A cos B + sin A sin B
                             Proved
 

Share this post on: